Keefektifan Dosis Ferri Klorida (FeCl3) Terhadap Penurunan Kadar Chemical Oxygen Demand (Cod) Pada Limbah Cair Etanol (CIU) Desa Bekonang Kecamatan Mojolaban Kabupaten Sukoharjo - Irsyadi, Maftuh Al, Dwi Astuti, SKM., M.Kes (2017)
COD levels in wastewater which indicates that the higher the degree of pollution on waters also high. The measurement results effluent COD concentration of ethanol amounted to 203,839.6 mg / l, this value exceeds a predetermined quality standards. Decreased levels of COD can be made by coagulation, flocculation and sedimentation using ferric chloride (FeCl3). The purpose of this study to determine the effectiveness of ferric chloride (FeCl3) in reducing the levels of COD in wastewater of ethanol. This research method is True Experiment with pretest posttest study design with Control Group. The population in this study is the liquid waste ethanol Bekonang Sukoharjo volume of wastewater each day ± 100-150 lliter / day. The number of samples used is 24 liters. Quota sampling technique sampling. Statistical test using One Way Anova with data analysis p-0.000 (p <0.000), so that Ha is accepted. Statistical test results showed the effectiveness of the coagulant dose of ferric chloride (FeCl3) in lowering levels of COD. Coagulant dose of ferric chloride (FeCl3) are most effective in lowering levels of COD in wastewater of ethanol was 6 g / l with efficacy of 74.1% (53123.2 mg / l)